2004
DOI: 10.17221/4342-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental phytase on performance and tibia ash of broilers fed different cereals based diets

Abstract: A 21-day experiment with day-old broilers was conducted in order to assess the effect of phytase supplementation to different cereals-soybean meal based diets on broiler performance and tibia ash. Diets were formulated to contain 4 different cereals (maize, wheat, triticale and barley), 2 levels of dietary calcium (0.6 and 1.0%) and 3 levels of supplemental phytase (0, 500 and 1 000 PU/kg). Supplemented phytase had beneficial effects on broiler performance. It significantly increased body weight gain (P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…In the present study, supplemental phytase did not influence tibia ash, which is in accordance with the results of Perney et al (1993) and Pintar et al (2004), but in contrast with those of Sohail and Roland (1999) and Woyengo et al (2010) from maize-soyabean based diets.…”
Section: Resultssupporting
confidence: 91%
“…In the present study, supplemental phytase did not influence tibia ash, which is in accordance with the results of Perney et al (1993) and Pintar et al (2004), but in contrast with those of Sohail and Roland (1999) and Woyengo et al (2010) from maize-soyabean based diets.…”
Section: Resultssupporting
confidence: 91%
“…In the preceding papers we showed that: (i) magnitude of the beneficial effect of phytase supplementation on broiler performance varied between different cereals and calcium levels, (ii) supplemental phytase reduced the excretion of phytate phosphorus and increased its retention, magnitude of the effect depended on calcium dietary level, (iii) tibia ash content was not influenced by supplemental phytase (Pintar et al, 2004(Pintar et al, , 2005. In this paper effects on the mineral content in tibia are presented.…”
mentioning
confidence: 77%
“…In the preceding paper we showed that the magnitude of beneficial effect of phytase supplementation on broiler performance varied between different cereals and calcium levels (Pintar et al, 2004). In this paper the effects on nitrogen, calcium, total and phytate phosphorus excretion and retention are presented.…”
mentioning
confidence: 87%